Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To determine the equation of the quadratic function [tex]\( f(x) \)[/tex] with roots [tex]\(-2\)[/tex] and [tex]\(3\)[/tex] and which passes through the point [tex]\((2, -4)\)[/tex], follow these steps:
1. General Form: Given that the function has roots [tex]\(-2\)[/tex] and [tex]\(3\)[/tex], we can write it in its factorized form:
[tex]\[ f(x) = a(x + 2)(x - 3) \][/tex]
where [tex]\( a \)[/tex] is a constant that we need to determine.
2. Substitution of the Point:
We know that the point [tex]\((2, -4)\)[/tex] lies on [tex]\( f(x) \)[/tex]. This means when [tex]\( x = 2 \)[/tex], [tex]\( f(x) = -4 \)[/tex].
Substitute [tex]\( x = 2 \)[/tex] and [tex]\( f(x) = -4 \)[/tex] into the equation:
[tex]\[ -4 = a(2 + 2)(2 - 3) \][/tex]
3. Solve for [tex]\( a \)[/tex]:
Simplify the expression:
[tex]\[ -4 = a(4)(-1) \][/tex]
[tex]\[ -4 = -4a \][/tex]
Divide both sides by [tex]\(-4\)[/tex]:
[tex]\[ 1 = a \][/tex]
4. Formulate the Final Equation:
Now that we know [tex]\( a = 1 \)[/tex], we substitute [tex]\( a \)[/tex] back into the factorized form:
[tex]\[ f(x) = (x + 2)(x - 3) \][/tex]
5. Conclusion:
Comparing this result with the given options, we find that the correct function is:
[tex]\[ f(x) = (x + 2)(x - 3) \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{(x+2)(x-3)} \][/tex]
1. General Form: Given that the function has roots [tex]\(-2\)[/tex] and [tex]\(3\)[/tex], we can write it in its factorized form:
[tex]\[ f(x) = a(x + 2)(x - 3) \][/tex]
where [tex]\( a \)[/tex] is a constant that we need to determine.
2. Substitution of the Point:
We know that the point [tex]\((2, -4)\)[/tex] lies on [tex]\( f(x) \)[/tex]. This means when [tex]\( x = 2 \)[/tex], [tex]\( f(x) = -4 \)[/tex].
Substitute [tex]\( x = 2 \)[/tex] and [tex]\( f(x) = -4 \)[/tex] into the equation:
[tex]\[ -4 = a(2 + 2)(2 - 3) \][/tex]
3. Solve for [tex]\( a \)[/tex]:
Simplify the expression:
[tex]\[ -4 = a(4)(-1) \][/tex]
[tex]\[ -4 = -4a \][/tex]
Divide both sides by [tex]\(-4\)[/tex]:
[tex]\[ 1 = a \][/tex]
4. Formulate the Final Equation:
Now that we know [tex]\( a = 1 \)[/tex], we substitute [tex]\( a \)[/tex] back into the factorized form:
[tex]\[ f(x) = (x + 2)(x - 3) \][/tex]
5. Conclusion:
Comparing this result with the given options, we find that the correct function is:
[tex]\[ f(x) = (x + 2)(x - 3) \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{(x+2)(x-3)} \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.